Evaluation of lymphatic flow pattern using indocyanine green fluorescence imaging in a highly metastatic mouse model. Issue 2 (22nd December 2020) - Yamamoto, Masashi; Taniguchi, Kohei; Tominaga, Tomo; Shibata, Masa‐Aki; Inomata, Yosuke; Komura, Kazumasa; Osumi, Wataru; Hamamoto, Hiroki; Tanaka, Keitaro; Okuda, Junji; Uchiyama, Kazuhisa
Abstract: Recently, the feasibility of real‐time indocyanine green (ICG) fluorescence imaging–guided complete mesocolic excision in colon cancer surgery has been demonstrated; however, its application to the evaluation of lymphatic flow in widespread lymph node metastasis is uncertain. This study aimed to evaluate lymphatic flow using the real‐time ICG fluorescence imaging. A mouse model of subcutaneous inoculation of BJMC3879Luc2 cells, which have been demonstrated to highly metastasize to the lymph nodes, was used as an evaluation model. Tumor growth and lymphatic flow were monitored weekly by bioluminescent imaging and near‐infrared (NIR) fluorescence imaging, respectively. After sacrificing the mice, lymph node metastases were evaluated by bioluminescent imaging and histopathology. Lymphatic flows in a model of high lymph node metastasis were evaluated using NIR fluorescence imaging. Pathological metastases of bilateral axillary, femoral, and para‐aortic lymph nodes were detected in all inoculated mice (100%: 5/5). Real‐time NIR fluorescence imaging showed the primary lymphatic vessels staining through the metastatic lymph nodes as before the inoculation of the cancer cells. Hitherto, it has been considered that lymphatic flow was changed using the bypass pathway due to occlusion of the primary lymphatic vessels. In this presented study, real‐time ICG fluorescence imaging showed no changes in lymphatic flow after lymph node metastasis. Our results suggest that real‐time ICG fluorescence imaging may have potential for the guidance of colon cancer surgery in cases of widespread lymph node metastasis. Abstract : This study aimed to evaluate lymphatic flow using real‐time indocyanine green fluorescence imaging in a highly metastatic mouse model.